The Description of CO Levels, COHb Levels, And Blood Pressure of Basement Workers X Shopping Centre, Malang - Khairina, Mahda (JURNAL KESEHATAN LINGKUNGAN, 2019)
CO is one of air pollutants that harmful to humans. CO that inhaled by humans will react with hemoglobin and forming COHb in the blood. The purpose of this research is describe the CO levels of basement, COHb levels, and blood pressure basement workers of X shopping center Malang. This research was observational research that was included in a cross sectional study. This research done by the interview with respondents that all of the 14 workers, related to the characteristics of the respondents, measured of the CO levels, examinated of COHb levels and measured of blood pressure. The average of CO levels at the basement work area was 23,93 ppm, less than the standard. 13 workers had high levels of COHb >5%. 9 of the 13 workers with high blood COHb levels had high blood pressure. Workers who had about 47-55 years old, working in the basement of > 6 years, and had a smoking habit tends to had high levels of COHb and high blood pressure. Preferably basement workers who every day exposed by the CO to stop smoking so as not to get exposure CO gas from smoking.